Micro-nutrient composition and end-user acceptable quality in potato in Ethiopia - Asfaw, A.; Woldegiorgis, G.; Kolech, S.A.; Mulugeta, G.; Mulugeta, D.; Ngugi, A.; Burgos, G.; Felde, T. zum; Bonierbale, Merideth W. (Informa UK Limited, 2018)
Micronutrient deficiencies in diets, including iron (Fe) and zinc (Zn), are an important public health problem across population in Ethiopia. Potato is a modest source of dietary nutrients. The purpose of this study was to assess the mineral (Fe & Zn) composition of potato germplasm in Ethiopia and grower's willingness to try new potato types. The Fe and Zn contents were assessed in peeled tubers of popular farmer varieties, and newly introduced Andean diploid group Phureja accessions and improved tetraploid clones grown in multi-location trials. Grower's preferences for the new potato types was assessed using a participatory approach. Significant variations in mineral and tuber yield traits exist among the germplasm assessed and broad-sense heritability appears to be high for most traits measured, suggesting that progress through breeding can be made among these materials. However, the slightly negative correlation of tuber yield with Fe and Zn content and user appreciation traits found in this study suggests that progress in improving crops for yield and enhanced Fe and Zn concentrations with end-user acceptable quality will be challenging. The results from this study provide baseline information on Fe and Zn composition of many popular farmer varieties in Ethiopia and end-user preference criteria for evaluating new potato varieties that would help to orient the biofortification breeding to the conditions and preference of farmers.